Estudo das ressonâncias na Sequenza IV de Lucio Berio - Daniel Lemos Cerqueira (2009)
The present work focus effects of resonance on Sequenza IV for piano by the italian composer Luciano Berio (1925-2003), assuming the hypothesis that the resonance is a structural material. Therefore, five excerpts were selected from the score and extracted from recordings of three chosen pianists. Fifteen spectral analysis were elaborated to illustrate results perceptible by listening, dealing with a discussion about the interpreters comprehension of the materials, particularities of the excerpts and their expected effects. This work also has an historical-cultural approach, establishing a dialog between the composers personal conceptions and musical ideas from his time, evidencing Sequenza IVs importance and its peculiarities inside the Sequenze cycle. Also, a brief study was made about the pedal mechanisms along the history, as well as its applications on the piano repertoire.